The Impact Of Certified Competency Tourism Human Resources In Facing The Aec Era: Case Study In Bali - Djati, Sundring Pantja; Sudjana, I Made; Darsana, I Made; Sudiarta, I Nyoman; Mahendra, I Wayan Eka (Jurnal Penelitian Pariwisata, 2022)
The tourism business in Bali is growing rapidly, and Bali has been known as one of the most popular tourist destinations, especially among foreign tourists. The combination of beauty and a balanced lifestyle strongly attracts foreign tourists to Bali. In anticipating the growth of tourists to Bali, human resources must be by the needs of the tourism industry. This article aims to determine Bali tourism human resources competency standards in the Masyarakat Ekonomi ASEAN. The data collection and analysis in this paper use literature studies, interviews, and observations of stakeholder activities related to implementing the competency certification process. The role of the government in preparing various regulations for improving human tourism resources through the Indonesian National Work Competency Standards, the Indonesian National Qualifications Framework, and Competency-Based Training, which are the main instruments in the competency certification process, are indispensable. In addition, it is also important to work with Professional Certification Institutions that have been certified nationally and internationally to strengthen the human resources of Bali tourism. Keywords: Certificate of Competence, Asean Economic Community, Certificate of Competence, Asean Economic Community, ASEAN Economic Community